Evidence of a thermo-diffusion pinch on particle transport in FTU discharges close to density limit. (August 2017) - Tudisco, O.; Meineri, C.; Apruzzese, G.; D'Arcangelo, O.; Giovannozzi, E.; Marinucci, M.; Mazzotta, C.; Pucella, G.; ,
Highlights: Experimental density profile evolution during the MARFE has been presented. The modification of the electron source term due to the presence of the MARFE has been examined. Simulation of the profile evolution has been obtained using a thermo-convective pinch. Abstract: In FTU, the density profile in the presence of large MARFE becomes more and more peaked with increasing density, forming strong density gradients close to the radial region affected by the MARFE. The temperature at the edge drops to few eV, driving a drop of the whole profile. The estimated particle source cannot justify the change of the density gradient, which instead is well-explained by a change of the pinch. A thermo-diffusion term well-describes the pinch evolution and the experimental behavior of the density at those radii where temperature measurements are reliable.